Role of ortho‐retronasal olfaction in mammalian cortical evolution. Issue 3 (11th June 2015) - Rowe, Timothy B.; Shepherd, Gordon M.
Abstract : Fossils of mammals and their extinct relatives among cynodonts give evidence of correlated transformations affecting olfaction as well as mastication, head movement, and ventilation, and suggest evolutionary coupling of these seemingly separate anatomical regions into a larger integrated system of ortho‐retronasal olfaction. Evidence from paleontology and physiology suggests that ortho‐retronasal olfaction played a critical role at three stages of mammalian cortical evolution: early mammalian brain development was driven in part by ortho‐retronasal olfaction; the bauplan for neocortex had higher‐level association functions derived from olfactory cortex; and human cortical evolution was enhanced by ortho‐retronasal smell. J. Comp. Neurol. 524:471–495, 2016. © 2015 Wiley Periodicals, Inc. Abstract : Evidence from paleontology and physiology suggests that ortho‐retronasal olfaction played a critical role at three stages of mammalian cortical evolution: early brain development was driven partly by ortho‐retronasal olfaction; the bauplan for neocortex had higher‐level association functions derived from olfactory cortex; and human cortical evolution was enhanced by ortho‐retronasal olfaction.